Systemising corpus-based definitions in second language lexicography - Renau, Irene; Alonso Campo, Araceli (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2017)
This study explores the application of a semantic analysis methodology to the creation of definitions of learners’ dictionaries. Defining words is a delicate art, traditionally left to the general writing skills of the lexicographer, introspection, or even intuition. In the past decades, many effort have been guided to systemise the technique, particularly in the pedagogical dictionaries momentum. In this paper, we try to demonstrate that there is still room for improvement, and that a systematic corpus analysis can be applied to build better explanations for the meaning of words. We explain the theoretical background chosen for our study, the associated methodology and five specific strategies which can direct the lexicographer through his/her task. In order to give a concrete example, we show our work with a Spanish dictionary project for foreign learners which is currently under development and has a core of very frequent Spanish verbs already available on the Internet.